Keabsahan Perjanjian Asuransi Melalui Telemarketing Ditinjau dari Undang-Undang Nomor 11 Tahun 2008 - Ilyas Ilyas (Universitas Syiah Kuala, 2012)
ABSTRACT: Insurance is an agreement between two or more parties that the payer binds inself to the paid by receiving premi for compensating the paid because of loss, damage or miss he benefit or the law responsibility of third party that might burdened the pid because of something that is not exactly happens or to compensate due to the death or life the paid as mentioned in Article 1 verse 1 of the Act Number 2, 1992. However, in its implementation the product is also sold by telemarketing through electronic media based on the Act Number 11, 2008 regarding Information and Electronic Transaction that an cause different views on when the validity of the agreement through the media. The Validity of Insurance Agreement Through Telemarketing Based on The Act Number 11, 2008